2023
DOI: 10.1002/dvg.23539
|View full text |Cite
|
Sign up to set email alerts
|

A temporally‐restricted pattern of endothelial cell collagen 4 alpha 1 expression during embryonic development determined with a novel knockin Col4a1‐P2A‐eGFP mouse line

Nathaniel L. Lartey,
Martijn van der Ent,
Roxann Alonzo
et al.

Abstract: SummaryClassical collagen type IV comprising of a heterotrimer of two collagen IV alpha 1 chains and one collagen IV alpha 2 chain is the principal type of collagen synthesized by endothelial cells (EC) and is a major constituent of vascular basement membranes. In mouse and man, mutations in genes that encode collagen IV alpha 1 and alpha 2 result in vascular dysfunction. In addition, mutations in genes that encode the Ephrin receptor B4 (EPHB4) and the p120 Ras GTPase‐activating protein (RASA1) that cause inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Moreover, our observations that dividing basal progenitor cells remain adhered to the BM during mitosis challenge the existing assumption that all dividing cells significantly reduce their adhesions to the BM ( Matus et al, 2014 ; Jones et al, 2019 ) and are in keeping with the integrin-rich contacts observed by Dix et al (2018) during cell division. Our FRAP experiments provide a proof-of-principle that the mTurq2-Col4a1 mouse line can be used to study and quantify COL4A1 mobility during assembly and our data agree with other studies demonstrating the highly stable nature of collagen IV within BMs, particularly the recent observations made by Lartey et al (2023) . The Col4a1-P2A-eGFP mouse line generated in their work labels cells that are actively secreting COL4A1 with eGFP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, our observations that dividing basal progenitor cells remain adhered to the BM during mitosis challenge the existing assumption that all dividing cells significantly reduce their adhesions to the BM ( Matus et al, 2014 ; Jones et al, 2019 ) and are in keeping with the integrin-rich contacts observed by Dix et al (2018) during cell division. Our FRAP experiments provide a proof-of-principle that the mTurq2-Col4a1 mouse line can be used to study and quantify COL4A1 mobility during assembly and our data agree with other studies demonstrating the highly stable nature of collagen IV within BMs, particularly the recent observations made by Lartey et al (2023) . The Col4a1-P2A-eGFP mouse line generated in their work labels cells that are actively secreting COL4A1 with eGFP.…”
Section: Discussionsupporting
confidence: 90%
“…The half-life of BM proteins in the Drosophila embryo has been measured to be on the order of ∼7–10 h ( Matsubayashi et al, 2020 ). Additionally, a recent study in mice found that active secretion of vascular BM COL4A1 could only be detected early in development, suggesting that secretion thereafter, throughout adult life, may occur at much lower levels ( Lartey et al, 2023 ). We therefore hypothesized that mTurq2-COL4A1 would be highly stable in the epidermal BM but may show increased mobility at E13.5 compared with E15.5 due to the rapid growth taking place during this earlier stage.…”
Section: Resultsmentioning
confidence: 99%